Responsiveness of raised pulmonary vascular resistance to oxygen assessed by pulsed Doppler echocardiography. Issue 4 (October 1991) - Vogel, M; Weil, J; Stern, H; Bühlmeyer, K
Abstract : OBJECTIVE–To assess whether changes in Doppler echocardiographic indices in the pulmonary artery correlated with changes in pulmonary vascular resistance. DESIGN–Acceleration time, ejection time, maximal flow velocity, and velocity time integrals were measured at the same time as pressure and oxygen saturation measurements in room air and during 10 minutes of oxygen breathing in the catheterisation laboratory. Pulmonary vascular resistance and pulmonary blood flow (Qp) were calculated from catheterisation data by use of the Fick principle. PATIENTS–14 consecutive patients with a congenital heart defect and a left to right shunt associated with raised pulmonary artery pressure who underwent routine diagnostic cardiac catheterisation to assess their pulmonary vascular resistance. RESULTS–Though pulmonary vascular resistance and systolic pulmonary artery pressure fell significantly during oxygen administration, there was no significant change in the acceleration time or ejection time. Peak velocity increased significantly during oxygen administration. During oxygen breathing Doppler derived measurements of pulmonary flow showed a significant increase in Qp similar to the increase in Qp measured by the Fick principle. There was no significant correlation between the fall in pulmonary vascular resistance and the increase in acceleration time or ejection time, increase in peak velocity, increase in pulmonary artery diameter, or increase in Doppler derived pulmonary blood flow. CONCLUSIONS–Measurements of acceleration and ejection time by Doppler echocardiography did not predict the response of pulmonary artery pressure and resistance to oxygen. Though changes in maximal flow velocity across the pulmonary artery and in Doppler derived pulmonary blood flow measurements became significant during oxygen breathing, the correlation of these changes with fall in pulmonary vascular resistance was poor.